The Expression of Programmed Death Ligand 1 and Vimentin in Resected Non-Metastatic Non-Small-Cell Lung Cancer: Interplay and Prognostic Effects - Bravaccini, Sara; Bronte, Giuseppe; Petracci, Elisabetta; Puccetti, Maurizio; D’Arcangelo, Manolo; Ravaioli, Sara; Tumedei, Maria Maddalena; Maltoni, Roberta; Delmonte, Angelo; Cappuzzo, Federico; Crinò, Lucio (Frontiers in Cell and Developmental Biology, 2021)
Programmed death ligand 1 (PD-L1) is an immune checkpoint with a role in cancer-related immune evasion. It is a target for cancer immunotherapy and its expression is detected for the use of some immune checkpoint inhibitors in advanced non-small cell lung cancer patients (NSCLC). Vimentin is a key component of the epithelial-to-mesenchymal transition phenotype. Its expression has negative prognostic effects in NSCLC. In this study, we retrospectively evaluated PD-L1 and vimentin expression in tumor cells, immune infiltrate and PD-L1 positive immune infiltrate via immunohistochemistry in tissue samples from resected non-metastatic NSCLC patients. We explored the interplay between PD-L1 and vimentin expression through Spearman’s correlation test. We performed univariate analysis through the Cox models for demographic and clinico-pathological variables, and also for dichotomized biomarkers, i.e. PD-L1 and vimentin in tumor cells, both with 1% and 50% cutoffs. We used Kaplan-Meier method to estimate the overall survival, comparing both vimentin and PD-L1 positive patients with all the others. We found a weak positive correlation between PD-L1 and vimentin expressions in tumor cells (r = 0.25; p = 0.001). We also observed a statistically not significant trend towards a shorter overall survival in patients with both PD-L1 and vimentin expression > 1% (HR = 1.36; 95% CI: 0.96-1.93, p = 0.087). In conclusion, these findings suggest that interplay between PD-L1 and vimentin may exist in non-metastatic NSCLC patients and the positivity of both markers in tumor tissue is associated with a trend towards a worse prognosis.